Framework-based Teacher Training Program: Cross-disciplinary Approaches in Early Childhood Education - Mohd Nazri Bin Abdul Rahman; Somayeh Mardomi; Reyhane Mardomi (Universitas Negeri Semarang, 2024)
Today in Malaysia, an increased focus is on the importance of qualified educators training in early childhood education (ECE) and its effects on young learner skill development. However, a significant obstacle to ECE educators' professional development includes a lack of professional training in teacher standards. The Teacher Training Program helps educators to understand children's characteristics (specifically from birth to age eight), parents, and communities. The structural framework addresses the areas for improvement and provides practical strategies for engaging, interdisciplinary learning environments. This study reflects and focuses on professional development findings from the Teacher Training Program (TTP) and centers around a framework to emphasize Malaysian preschool teacher challenges in implementing cross-disciplinary STEM education in early childhood activities. Researchers in this study used a library research method by searching relevant keywords in indexes and full-text resources (online and print sources) as a data collection method. This study attempts to indicate and highlight this program's cross-disciplinary STEM education role in preparing teachers.